2023
DOI: 10.1177/87552930231174244
|View full text |Cite
|
Sign up to set email alerts
|

Select liquefaction case histories from the 2001 Nisqually, Washington, earthquake: A digital data set and assessment of model performance

Abstract: While soil liquefaction is common in earthquakes, the case-history data required to train and test state-of-practice prediction models remains comparatively scarce, owing to the breadth and expense of data that comprise a single case history. The 2001 Nisqually, Washington, earthquake, for example, occurred in a metropolitan region and induced damaging liquefaction in the urban cores of Seattle and Olympia, yet case-history data have not previously been published. Accordingly, this article compiles 24 cone-pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Yet of the 75 papers reviewed, just one tested for statistical significance. Meanwhile, analyses of tier-2 SOP liquefaction models have shown that measured differences between models are rarely significant in individual earthquakes (Rasanen et al, 2023) or even within global compilations of several hundred case histories (Geyin et al, 2020). Unless proven otherwise, presented differences between AI models and SOP models are likely too small and/or too uncertain to be statistically significant.…”
Section: Recurrent Shortcomings (Why Existing Ai Liquefaction Models ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet of the 75 papers reviewed, just one tested for statistical significance. Meanwhile, analyses of tier-2 SOP liquefaction models have shown that measured differences between models are rarely significant in individual earthquakes (Rasanen et al, 2023) or even within global compilations of several hundred case histories (Geyin et al, 2020). Unless proven otherwise, presented differences between AI models and SOP models are likely too small and/or too uncertain to be statistically significant.…”
Section: Recurrent Shortcomings (Why Existing Ai Liquefaction Models ...mentioning
confidence: 99%
“…That is, some models are tested only on their ability to mimic an SOP model and not on their ability to predict liquefaction, yet SOP models are both statistically and conceptually far from perfect (e.g. Geyin et al, 2020; Rasanen et al, 2023; Upadhyaya et al, 2023).…”
Section: Recurrent Shortcomings (Why Existing Ai Liquefaction Models ...mentioning
confidence: 99%
“…An in-depth geological and geotechnical analysis of the whole area affected by liquefaction as a result of the 2012 Emilia earthquakes is shown in the Infrastructures 2023, 8, 133 2 of 15 study of Minarelli et al [6]. Liquefaction case histories observed during the 2001 Nisqually (Washington) earthquake are presented by Rasanen et al [7]. Other earthquakes during which such phenomena were observed occurred in Japan [8,9], Chile [10], Turkey [11] or Ecuador (gravelly soil liquefaction phenomena) [12].…”
Section: Introductionmentioning
confidence: 99%